Feminist Africa 15 Legal Voice: Special issue - Tamale, Sylvia; Bennett, Jane (Feminist Africa, 2011)
Feminist struggles in Africa are fought from various fronts, with the law representing but one of them. While law and judicial reforms are not a panacea gender inequalities, the legal front is a central plank in this struggle as both shield and sword—a shield to protect women against discrimination and the violation of their fundamental rights, and a sword to challenge and overturn unjust sexist practices and to effect fundamental change to the status quo. While by no means a magic bullet the law can indeed be a critical game changer in the gender political landscape.